2020
DOI: 10.3390/jof6030159
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Production by Stachybotrys chartarum Genotype S on Different Culture Media

Abstract: Stachybotrys (S.) chartarum had been linked to severe health problems in humans and animals, which occur after exposure to the toxic secondary metabolites of this mold. S. chartarum had been isolated from different environmental sources, ranging from culinary herbs and improperly stored fodder to damp building materials. To access the pathogenic potential of isolates, it is essential to analyze them under defined conditions that allow for the production of their toxic metabolites. All Stachybotrys species are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 41 publications
9
19
0
Order By: Relevance
“…Reliable protocols are needed to determine the ability of individual isolates to produce MT and thereby evaluate their hazard potential. Apart from cellulosecontaining media, potato dextrose agar (PDA) was shown to be an excellent medium for MT production [27], but the nutritional factors that govern MT production have not been identified yet. Temperature and humidity have been shown to influence MT production, but the underlying mechanisms and regulatory genes are still unknown [6,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Reliable protocols are needed to determine the ability of individual isolates to produce MT and thereby evaluate their hazard potential. Apart from cellulosecontaining media, potato dextrose agar (PDA) was shown to be an excellent medium for MT production [27], but the nutritional factors that govern MT production have not been identified yet. Temperature and humidity have been shown to influence MT production, but the underlying mechanisms and regulatory genes are still unknown [6,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by other authors [63] have shown the effect of the culture medium on the production of Stachybotrys chartarum mycotoxins. The highest concentrations of macrocyclic trichothecenes were determined on the PDA medium; the MEA medium was the intermediate medium.…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, Penicillium family members are fairly common in all types of buildings, and only some of them produce toxins [ 49 , 50 ], explaining the variable responses we observed. In addition, it should be noted that mycotoxin production depends on the metabolic activity and growth phase of fungi, so not even the pathogenic species produce toxins all the time, but only under certain conditions [ 51 ].…”
Section: Discussionmentioning
confidence: 99%